Sistem Monitoring Nyamuk Demam Berdarah dengan Ovitrap Berbasis Internet of Things (IoT) - Yulianto, Andik; Hadi, Hadi; Ma'muriyah, Ni'matul (INTEGER: Journal of Information Technology, 2024)
This study proposes the concept of IoT-based ovitrap as an innovative solution to control the spread of Dengue Fever (DF) in Batam. Utilizing a flexible-access ovitrap monitoring application via smartphones or computers, the Prototype method is employed as the basis for application implementation, with testing conducted to ensure its effectiveness. The hardware system consists of ESP32-cam collecting data from DHT11 sensors and camera, where the data is stored, processed, and then sent to the database. The software is designed to allow manual data input and monitoring through a web application, with Firebase Firestore Database serving as the data storage medium. Data collection methods involve direct observation of IoT-based ovitraps and related technology studies. Through automatic monitoring of temperature, humidity, and calculation of ABJ Container Index, the system aims to effectively reduce the number of DF cases.